How could the drug procurement procedure be improved to ensure good quality drugs, at the right time, in the required quantities and at an advantageous cost? The Ecuadorian case - Meythaler Galarza, Beatriz (2022)
The public procurement process is used by countries, especially developing countries, to obtain medicines of good quality, on time, at an affordable price and in the quantities necessary for the benefit of the population. In this way, states safeguard the right to health of their populations. Unfortunately, public procurement is subject to mismanagement and corruption, leading to price inflation, the distribution of poor quality drugs, shortages and waste, with final consequences for the poor and vulnerable. For this reason, this document will analyze how to transform an inefficient public procurement system into one that effectively meets the needs of the population and does not violate citizens' right to health. The analysis will be based on the Ecuadorian case, characterized by serious flaws. To this end, this paper will review the existing literature on the factors influencing the efficiency of public procurement and the characteristics of an efficient public procurement system to determine how our public procurement systems can be improved to ensure timely and cost-effective access. to drugs efficiently. JEL CODE: D73, K4